Index-based livestock insurance schemes to manage climate risks in Ethiopia: determinants of farmer’s willingness to pay and lessons learned from Dasenech district, South Omo - Melketo, Tagesse; Tolossa, Degefa; Abi, Meskerem; Bedeke, Sisay; Fentaw, Tenaw (Frontiers in Climate, 2025)
Livestock insurance, an important risk management tool, is gaining popularity in Ethiopia. Proper investigation is needed to expand its adaptability throughout the country. This study was designed to explore the willingness and payment capacity of farmers in Southern Ethiopia to pay for index-based livestock insurance as an alternative solution to climate risk mitigation. A mixed research method was employed to gather data from primary and secondary sources. Cross-sectional data were obtained from 157 cattle farmers, drawn randomly from the study area. The study also used key informant interviews and focus group discussions to collect qualitative data. Descriptive statistics, inferential tests, and double-hurdle model were used to analyze quantitative data. Word descriptions and thematic analysis were employed for qualitative data analysis. The results of the study showed that a significant proportion of farmers were willing to pay for IBLI services. The findings also suggested that the demand for index-based livestock insurance seemed to be influenced by a number of factors. Those households that are headed by a men, who are better educated, who are better experienced in farming system, and those who have access to credit and training are more likely to pay for the insurance. Farmers’ perception of weather-related risks and awareness about insurance also influenced farmers’ willingness to pay positively. Furthermore, farmers with larger assets, such as land and livestock, have more confidence in paying capacity for insurance. Farmers with mass media access were more likely to pay for IBLI. However, households with larger number of household members and those who perceived the cost of the insurance premium as unaffordable are less likely to purchase the IBLI. These significant factors impacting households’ willingness to pay for the insurance services must be considered in adaptation pathways. The Dasenech district case study suggests that IBLI can effectively mitigate climate risks and be applied to other regions with similar socioeconomic characteristics and production systems.